2018
DOI: 10.1007/s00203-018-1491-5
|View full text |Cite
|
Sign up to set email alerts
|

Varying susceptibility of clinical and environmental Scedosporium isolates to chemical oxidative stress in conidial germination

Abstract: Scedosporium species are opportunistic pathogens causing a great variety of infections in both immunocompetent and immunocompromised individuals. The Scedosporium genus ranks the second among the filamentous fungi colonizing the airways of patients with cystic fibrosis (CF), after Aspergillus fumigatus, and most species are capable to chronically colonize the respiratory tract of these patients. Nevertheless, few data are available regarding evasion of the inhaled conidia to the host immune response. Upon micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Therefore, the mechanisms allowing the conidia to evade the host immune response, mainly represented by the oxidative burst response of phagocytes and the production of ROS, are essential for a successful colonization process. Recently, we showed that Scedosporium species were able to germinate in oxidative stress conditions [ 36 ]. In addition, analysis of the S. apiospermum genome revealed the presence of 33 genes encoding putative enzymes possibly involved in the degradation of ROS or RNS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the mechanisms allowing the conidia to evade the host immune response, mainly represented by the oxidative burst response of phagocytes and the production of ROS, are essential for a successful colonization process. Recently, we showed that Scedosporium species were able to germinate in oxidative stress conditions [ 36 ]. In addition, analysis of the S. apiospermum genome revealed the presence of 33 genes encoding putative enzymes possibly involved in the degradation of ROS or RNS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%